IDNLearn.com: Your trusted platform for finding precise and reliable answers. Explore thousands of verified answers from experts and find the solutions you need, no matter the topic.
Sagot :
To solve for [tex]\( x \)[/tex] in the equation
[tex]\[ \frac{1}{2} - x + \frac{3}{2} = x - 4, \][/tex]
follow these steps:
1. Simplify the left-hand side:
Combine the constants [tex]\( \frac{1}{2} \)[/tex] and [tex]\( \frac{3}{2} \)[/tex]:
[tex]\[ \frac{1}{2} + \frac{3}{2} = \frac{4}{2} = 2. \][/tex]
So the equation simplifies to:
[tex]\[ 2 - x = x - 4. \][/tex]
2. Rearrange the equation to isolate [tex]\( x \)[/tex]:
Add [tex]\( x \)[/tex] to both sides of the equation to eliminate the [tex]\( -x \)[/tex] term on the left-hand side:
[tex]\[ 2 - x + x = x - 4 + x, \][/tex]
which simplifies to:
[tex]\[ 2 = 2x - 4. \][/tex]
3. Isolate the [tex]\( x \)[/tex] term:
Add 4 to both sides of the equation to move the constant term on the right-hand side to the left:
[tex]\[ 2 + 4 = 2x, \][/tex]
which simplifies to:
[tex]\[ 6 = 2x. \][/tex]
4. Solve for [tex]\( x \)[/tex]:
Divide both sides by 2 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{6}{2} = 3. \][/tex]
Therefore, the solution for [tex]\( x \)[/tex] is [tex]\( 3 \)[/tex].
Given the choices, the correct answer is:
A. [tex]\( x = 3 \)[/tex]
[tex]\[ \frac{1}{2} - x + \frac{3}{2} = x - 4, \][/tex]
follow these steps:
1. Simplify the left-hand side:
Combine the constants [tex]\( \frac{1}{2} \)[/tex] and [tex]\( \frac{3}{2} \)[/tex]:
[tex]\[ \frac{1}{2} + \frac{3}{2} = \frac{4}{2} = 2. \][/tex]
So the equation simplifies to:
[tex]\[ 2 - x = x - 4. \][/tex]
2. Rearrange the equation to isolate [tex]\( x \)[/tex]:
Add [tex]\( x \)[/tex] to both sides of the equation to eliminate the [tex]\( -x \)[/tex] term on the left-hand side:
[tex]\[ 2 - x + x = x - 4 + x, \][/tex]
which simplifies to:
[tex]\[ 2 = 2x - 4. \][/tex]
3. Isolate the [tex]\( x \)[/tex] term:
Add 4 to both sides of the equation to move the constant term on the right-hand side to the left:
[tex]\[ 2 + 4 = 2x, \][/tex]
which simplifies to:
[tex]\[ 6 = 2x. \][/tex]
4. Solve for [tex]\( x \)[/tex]:
Divide both sides by 2 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{6}{2} = 3. \][/tex]
Therefore, the solution for [tex]\( x \)[/tex] is [tex]\( 3 \)[/tex].
Given the choices, the correct answer is:
A. [tex]\( x = 3 \)[/tex]
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.